PENDEKATAN SISTEM DALAM MANAJEMEN PENDIDIKAN - Santika, Desi; Diana Nafisa Sabila Haq; Romlah; Saiful Anwar; Ilham Fatoni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to evaluate the objectives and benefits of studying a systems approach in educational management. A systems approach helps understand the interrelationships between various elements in the education system, such as students, teachers, curriculum, and facilities, as well as the mutual impacts between them. This approach primarily aims to improve the effectiveness of educational management through in-depth analysis to create more appropriate policies and sustainable solutions. Some of the benefits are improving the quality of management, optimizing resources, making more precise decisions, and handling complex educational challenges more systematically. This research method is a literature review, where the researcher identifies, collects, and examines relevant scientific works to gain an in-depth understanding of the topic without directly collecting primary data.